P55PIK Transcriptionally Activated by MZF1 Promotes Colorectal Cancer Cell Proliferation. (12th September 2012) - Deng, Yu; Wang, Jing; Wang, Guihua; Jin, Yuan; Luo, Xuelai; Xia, Xianmin; Gong, Jianping; Hu, Junbo
Abstract : p55PIK, regulatory subunit of class IA phosphatidylinositol 3-kinase (PI3K), plays a crucial role in cell cycle progression by interaction with tumor repressor retinoblastoma (Rb) protein. A recent study showed that Rb protein can localize to the mitochondria in proliferative cells. Aberrant p55PIK expression may contribute to mitochondrial dysfunction in cancer progression. To reveal the mechanisms of p55PIK transcriptional regulation, the p55PIK promoter characteristics were analyzed. The data show that myeloid zinc finger 1, MZF1, is necessary for p55PIK gene transcription activation. ChIP (Chromatin immuno-precipitation) assay shows that MZF1 binds to the cis-element "TGGGGA" in p55PIK promoter. In MZF1 overexpressed cells, the promoter activity, expression of p55PIK, and cell proliferation rate were observed to be significantly enhanced. Whereas in MZF1-silenced cells, the promoter activity and expression of p55PIK and cell proliferation level was statistically decreased. In CRC tissues, MZF1 and p55PIK mRNA expression were increased (P = 0.046, P = 0.047, resp.). A strong positive correlation (Rs = 0.94 ) between MZF1 and p55PIK mRNA expression was observed. Taken together, we concluded that p55PIK is transcriptionally activated by MZF1, resulting in increased proliferation of colorectal cancer cells.